2018
DOI: 10.1140/epjc/s10052-018-5999-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel subjet observables for jet quenching in heavy-ion collisions

Abstract: Using a novel observable that relies on the momentum difference of the two most energetic subjets within a jet ΔS 12 we study the internal structure of highenergy jets simulated by several Monte Carlo event generators that implement the partonic energy-loss in a dense partonic medium. Based on inclusive jet and dijet production we demonstrate that ΔS 12 is an effective tool to discriminate between different models of jet modifications over a broad kinematic range. The new quantity, while preserving the colline… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 63 publications
(106 reference statements)
0
29
0
Order By: Relevance
“…Elastic energy loss is not important since the parton is very energetic, and inelastic scattering is extremely rare due to the very short formation time of the first vacuum-like splitting. On top of energy loss, QGP inter- actions also induce jet collimation, an effect that has already been observed in other observables [13,34,35]. The surviving jets in PbPb collisions are biased towards having a hard (vacuum-like) fragmentation pattern, which is correlated to larger formation times.…”
Section: Comparison Of τ and C/a Reclustering Algorithms For Jet Quenching Studiesmentioning
confidence: 75%
“…Elastic energy loss is not important since the parton is very energetic, and inelastic scattering is extremely rare due to the very short formation time of the first vacuum-like splitting. On top of energy loss, QGP inter- actions also induce jet collimation, an effect that has already been observed in other observables [13,34,35]. The surviving jets in PbPb collisions are biased towards having a hard (vacuum-like) fragmentation pattern, which is correlated to larger formation times.…”
Section: Comparison Of τ and C/a Reclustering Algorithms For Jet Quenching Studiesmentioning
confidence: 75%
“…Jet sub-structure at STAR Raghav Kunnawalkam Elayavalli for the STAR Collaboration In our studies, we found the groomed jet radii (R g ) to be highly sensitive to the fluctuating underlying event in Au+Au collisions and therefore we devised a new observable involving subjets of a smaller radius reconstructed within the original jet (see here [13]…”
Section: Pos(high-pt2019)026mentioning
confidence: 99%
“…The Au+Au data used in these proceedings were collected during the 2007 run with its corre- In our studies, we found the groomed jet radii (R g ) to be highly sensitive to the fluctuating underlying event found in Au+Au collisions and therefore we devised a new observable involving sub-jets of a smaller radius reconstructed within the original jet (see here [11] for a recent theoreti- We also observe a remarkable difference in the shape of z SJ when compared to that of the SoftDrop z g , which is caused by selecting the core of the jet. The θ SJ for jets within the considered p T range peaks at small values and includes a natural lower cutoff at the sub-jet radius and we now select jets based on this distribution.…”
Section: Jet Angular Scale In Au+au Collisionsmentioning
confidence: 99%